Association between chinese medicine body constitution and variants in metabolic gene (rs1501299 & rs1801282) - Fong, Yu Qi (2022)
Chinese Medicine Body Constitution (CMBC) classifies people into nine types based on physical, mental features and different disease susceptibility. Early classification of CMBC may prevent disease onset by providing prophylactic treatment, especially for metabolic disorder which is highly associated with lifestyle factors. Metabolic disorders are a group of diseases with abnormal biochemical pathway. There is a high risk of metabolic disorder development among Malaysian population, which evaluated by prevalence of metabolic syndrome (43.4%). This study was to investigate the association between specific CMBC types and risk of metabolic disorder development, which measured using metabolic risk factors (MRFs) and metabolic gene variants. A total of 85 subjects had been recruited and classification of CMBC type was assessed using CMBC questionnaire. Blood sampling had been carried out and DNA was extracted for genotyping of metabolic gene variant rs1501299 and rs1801282. MRFs including fasting blood glucose (FBG), total cholesterol level, blood pressure and waist circumference were measured. SPSS 22.0 was used for data analysis. Gentleness showed as the highest prevalence while Yin deficiency and Qi deficiency were the predominant biased CMBC type in population studied. The prevalence of MRFs found to be 8.3% (prediabetes), 15.3% (central obesity), 12.9% (hypertension) and 41.2% (hypercholesterolemia). The rs1501299 was a significant variant while rs1801282 was an insignificant variant among Malaysian population. Hypertension and Log10FBG were found associated with CMBC type at 90% significant level. Hypertension was positively associated with Yin deficiency while Yang deficiency showed no correlation with prediabetes. There was no significant difference among genotypes of rs1501299 and rs1801282 with CMBC types, which may not be a conclusive finding due to small sample size. Larger sample size and involvement of more MRFs are suggested in further study. In conclusion, CMBC may be used as a significant tool in assessing the predisposition towards certain diseases.